KEDUDUKAN ANAK DARI PERNIKAH SIRI DALAM HUKUM ISLAM DI INDONESIA - Safar Alim (Yayasan Baitul Hikmah al-Zain, 2026)
Development of a modern period and globalization have increased various social interaction. Such interaction may vary from free sex to unregistered marriage to cover disgrace. The status of children resulted in unregistered marriage is not clear in society whether they are legitimate or not, especially in terms of inheritance. There are three laws of inheritance prevailing in Indonesia, each has advantages and disadvantages, as well as different purpose. This research proposes to reveal the status of children resulted from unregistered marriage in accordance with the Indonesia positive laws, and that according to Islamic Law. This research is a legal research. The approach used is the statutory approach by reviewing the laws related to the inheritance of unregistered marriage, and comparative approach by comparing two existing inheritance laws in Indonesia, that is civil law and Islamic law. Children from unregistered marriage Have the same position as legitimate children in Indonesian law Nevertheless, there are two things that make difference, that is in term of identity and in inheritance, children from unregistered marriage Have the same position and part of inheritance as legitimate children, provided that the children have been authorized. While in Islamic law, children from the unregistered marriage and legitimate marriage have the same position although they have not been authorized. In both perspectives, marriage should be registered and get a certificate, otherwise, the children are categorized as those of outside marriage. So that, without recording a child’s identity, that children considered outsider child.